ADSORPSI PENCEMARAN LIMBAH CAIR INDUSTRI PENYAMAKAN KULIT OLEH KITOSAN YANG MELAPISI ARANG AKTIF TEMPURUNG KELAPA - Musrowati Lasindrang (Jurnal Teknosains, 2014)
Chitosan has been used as biosorbent. In addition to having advantages, chitosan as biosorbent also has disadvantages. Chitosan is very soluble in low pH, so it cannot adsorb Cr (total) at low pH. It is because the active site (amine group) of chitosan undergoes protonation, and its adsorption capability is easily influenced by anions in waters. Therefore, this research studied the use of chitosan coating on active charcoal of coconut shell to increase the adsorption capability of Cr (total), BOD, and COD. This research was done to evaluate the characteristics of the liquid waste quality with or without Wastewater treatment unit (IPAL), and compare them with the Regulation of DIY Governor number 7/2010. It also studied the effect of pH and Concentration of chitosan coating on active charcoal as adsorbent on the decrease of Cr (total), BOD, and COD concentration in the liquid waste of leather tanning. The results indicate that the liquid waste of the leather tanning industry with and without Wastewater treatment unit (IPAL) have exceeded the quality standard for the liquid waste of leather tanning industry. An ANOVA statistical test indicated that Cr (total), BOD, and COD are significant at 0.05 (p < 0.05), with various pH influencing the decrease in Cr (total), BOD, and COD. The highest removal percentage resulting from the effect of chitosan concentration coating on active charcoal is obtained in adsorbent C (K3A1), with Cr (total) (91.9%); BOD (99.5%); and COD (98.47%).;